The failure to overcome trauma: “Eyes” as a silent and silenced victim in the juvenile novel Heaven (2022) - Rakhmawati, Yulia; Sudarmaji, Sudarmaji (LITERA, 2026)
Realistic depiction and representation of harsh reality of life have markedly emerged in children’s literature. In the age of global conversation around bullying and sexual violence, investigating trauma—formerly a forbidden, delicate topic—has gained crucial momentum. Accordingly, this study (1) examines Eyes’ traumatic disorders in Heaven (2022) by Mieko Kawakami, and (2) unveils his result of trauma recovery journey. Applying a descriptive-qualitative approach, data were gathered through systematic close reading and note-taking and interpreted according to Judith Herman’s theory of trauma. It is revealed that Eyes’ trauma stems from chronic emotional and physical bullying, as well as non-direct sex violence, leading to extreme disassociation. His recuperation is represented as incomplete and precarious. There are moments of safety through a comforting letter-writing, yet they are unstable. Remembrance and mourning stages are constrained, as exemplified by a lack of self-consciousness, an absence of empathy from others, and no professional help. Reconnection falls through when he chooses a physical transformation through eye surgery over emotional recovery and relational reconciliation. To conclude, “Eyes” is an example of a silent and silenced trauma victim, whose continuous anonymity throughout the entire story functions as a form of personal, social, and narrative erasure, indicating unsuccessful trauma recovery. From this novel, the significance of performing open and honest discussion supportive environment, and empathetic team—among peers, between students-teachers, children-parents, and general public—emerge as a set of central educational message.